2011
DOI: 10.1523/jneurosci.5265-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Temporally Specified Genetic Ablation of Neurogenesis Impairs Cognitive Recovery after Traumatic Brain Injury

Abstract: Significant spontaneous recovery occurs following essentially all forms of serious brain injury, though the mechanisms underlying this recovery are unknown. Given that many forms of brain injury such as traumatic brain injury (TBI) induce hippocampal neurogenesis, we investigated whether these newly generated neurons might play a role in recovery. By modeling TBI in transgenic mice, we determined that injury-induced newly generated neurons persisted over time and elaborated extensive dendritic trees that stabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
176
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(185 citation statements)
references
References 57 publications
8
176
1
Order By: Relevance
“…This is consistent with the findings of some studies [61,62], although in others, an increase in progenitors and neurogenesis has been reported [29,39,63,64]. Interestingly, similar to our PSA-NCAM1 population results, a study by Yu et al [65] reported a loss of intermediate (Dcx1) progenitors early after injury in mice, which recovered over several days; however, the percentage of new intermediates (Dcx1/BrdU1) at 7 days was increased, dissimilar to our observations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…This is consistent with the findings of some studies [61,62], although in others, an increase in progenitors and neurogenesis has been reported [29,39,63,64]. Interestingly, similar to our PSA-NCAM1 population results, a study by Yu et al [65] reported a loss of intermediate (Dcx1) progenitors early after injury in mice, which recovered over several days; however, the percentage of new intermediates (Dcx1/BrdU1) at 7 days was increased, dissimilar to our observations.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, similar to our PSA-NCAM1 population results, a study by Yu et al [65] reported a loss of intermediate (Dcx1) progenitors early after injury in mice, which recovered over several days; however, the percentage of new intermediates (Dcx1/BrdU1) at 7 days was increased, dissimilar to our observations. There and in subsequent studies [29,64], the same laboratory observed an injury-induced increase in proliferation of early (nestin1) progenitors which resulted in long-term increases in new neurons. Partially consistent with this, we observed increased nuclear signal for the early progenitor protein Sox2 following injury; however, the overall long-term outcome was instead a diminution of surviving neurons generated in the postinjury period.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…To better understand the role of neurogenesis in spontaneous recovery following trauma, Kernie and colleagues again used the nestin-HSV-TK GFP transgenic model [87]. Continuous administration of ganciclovir for 4 weeks following CCI ablated 90% of injury-induced hippocampal neurogenesis by 2 months after TBI without affecting astrogliosis.…”
Section: Neurogenesismentioning
confidence: 99%